2010
DOI: 10.1055/s-0029-1246161
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Persisting CSF Leaks Following Standard or Extended Endoscopic Transsphenoidal Surgery for Pituitary Tumor

Abstract: More complex defects after pituitary surgery should be repaired with a multilayer technique, using autologous materials such as fat, fascia lata, bone and mucoperiosteum taken from the middle turbinate. This type of autologous material is generally reliable in more complex defects, and it appears to be easy to harvest and handle for repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 22 publications
0
50
0
2
Order By: Relevance
“…Surgical repair of skull base defects during the EETS procedure is an important and necessary step to prevent postoperative complications, and to provide anatomic integrity (23). The most common serious potential complication of EETS is cerebrospinal fluid (CSF) leakage that could result in disasterous intracranial complications such as meningitis or pneumocephalus (28,33). A history of previous surgery or radiation exposure, obesity, a large duramater defect, opening of cisterns or ventricles during the surgery, a large volume of tumor resection, leaving a residual tumor and incompliance of the patient during the postoperative period are factors that may increase the risk of postoperative CSF leakage (33).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical repair of skull base defects during the EETS procedure is an important and necessary step to prevent postoperative complications, and to provide anatomic integrity (23). The most common serious potential complication of EETS is cerebrospinal fluid (CSF) leakage that could result in disasterous intracranial complications such as meningitis or pneumocephalus (28,33). A history of previous surgery or radiation exposure, obesity, a large duramater defect, opening of cisterns or ventricles during the surgery, a large volume of tumor resection, leaving a residual tumor and incompliance of the patient during the postoperative period are factors that may increase the risk of postoperative CSF leakage (33).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports describing methods and strategies for reconstruction of a dural defect in the sellar floor and the skull base 2,3,4,5,6,7,8 . The utility of a pedicled nasoseptal flap 9 for the reconstruction of a large dural defect has recently become more widely accepted, but reports have included a variety of pathologies, approaches and reconstruction techniques 6,8,10 . To minimize the risk of postoperative CSF fistula, we have used a pedicled nasoseptal flap for pituitary adenomas, as well as for skull base tumors 11,12 .…”
mentioning
confidence: 99%
“…Furthermore no studies have directly compared these strategies. Some authors have described their own protocols for reconstruction of the sella according to the tumor extension or intraoperative findings 2,3,4,5,8 ; however, the pedicled nasoseptal flap was not included as an option in these other protocols. Since Hadad et al 9 described vascular pedicle nasoseptal flap as a novel reconstruction technique in 2006 (Hadad-Bassagasteguy flap; HBF), it has been reported that this flap can function well to separate the intradural space from the nasosinusal cavity 6,10,11,12,15 .…”
mentioning
confidence: 99%
“…and/or some form of rigid/semi-rigid buttressing (nasal septum, sphenoid bone, titanium mesh, biodegradable plates or Foley catheter). The use of vascularized mucosal flaps, dural substitutes and tissue sealants are also described (1,2,5,6,8, 18,22). Even primary suturing of the dural defects has been reported (10).…”
Section: Discussionmentioning
confidence: 99%